2020
DOI: 10.1515/bjes-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Brokers in Biotechnology and Software Networks in EU Research Projects

Abstract: Researchers have acknowledged that the flow of knowledge is influenced by the non-structural and structural features of networks. This paper aims to further develop an understanding of the institutional and structural features of knowledge networks by relating the brokerage roles of actors to the types and locations of organisations in biotechnology and software networks. The study is set within the context of the European Union (EU) research and innovation policy. It is designed as a social network analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The results of the research showed that prior acquaintance between the faculty members and the policymakers was mainly due to personal familiarity, and more than half of the connections were expressed and channeled through being a colleague, having a history of working together in an advisory committee, professor-student relationship, friendship and classmate relationship. As Kotim et al also showed, actors are more likely to cooperate in the network when they have already cooperated [ 35 ]. Jessani et al also showed that policymakers prefer to get the experts' opinions through personal and trusted contacts.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the research showed that prior acquaintance between the faculty members and the policymakers was mainly due to personal familiarity, and more than half of the connections were expressed and channeled through being a colleague, having a history of working together in an advisory committee, professor-student relationship, friendship and classmate relationship. As Kotim et al also showed, actors are more likely to cooperate in the network when they have already cooperated [ 35 ]. Jessani et al also showed that policymakers prefer to get the experts' opinions through personal and trusted contacts.…”
Section: Discussionmentioning
confidence: 99%